Clustering of Ionospheric Irregularities based on Spatiotemporal ROTI Keogram Images - Gleb Mutasov; Lin Min Min Myint; Pornchai Supnithi; Jirapoom Budtho; Napat Tongkasem; Michi Nishioka (My University, 2024)
Ionospheric irregularities associated with Equatorial plasma bubbles (EPB) can significantly impact navigation and communication systems. Therefore, their occurrences need to be studied and predicted. To solve the prediction problem, it is necessary to identify types of spatiotemporal characteristics as reference points for the predictive model. This work employs unsupervised machine learning algorithms to identify types of ionospheric irregularities due to EPB using the rate of total electron content index (ROTI) keograms. Two machine learning methods: two models, the Gaussian mixture model (GMM), and k-means, are considered. Comparative analysis is performed, and the optimal number of clusters is estimated using one classical, k-means and one additional - repeatability score, introduced in this work metric. The optimal GMM model successfully classifies three types of irregularity patterns offering valuable insights for the development of an effective EPB prediction model and enhancing our understanding of ionospheric behavior.
Keywords: Geophysics and Gravity Measurements; Geomagnetism and Paleomagnetism Studies